SEWAGE TREATMENT METHOD - KAWABE MASAO; SENZAKI TETSUO (2000)
PROBLEM TO BE SOLVED: To provide a treatment method for cleaning sewage discharged from the fishery processing industry or the livestock industry by food processing microorganisms and soil microorganisms. SOLUTION: A pollution causing substance in sewage is passed through microorganism carriers such as lapilli or coal ash of a thermal power plant to be collected and made large in size to be removed while sewage is cleaned by the action of microorganisms and the pollution causing substance collected in a space is decomposed by small animals propagated in soil covering.